A study of mydriatic effect on intraocular pressure and anterior chamber angle morphology by anterior segment optical coherence tomography - Srinivasapuram Krishnacharya Prabhakar; Meghana Hiremath (Journal of the Egyptian Ophthalmological Society)
Context Pharmacological mydriasis possibly is associated with intraocular pressure (IOP) rise and anterior chamber angle changes. Hence, this study is focused on pressure analysis with anterior segment optical coherence tomography measurements of angle parameters during various dilation phases. Aims Purpose is to investigate IOP variations during dilation phases and to discover association of anterior segment optical coherence tomography measurements. Settings and design Observational study. Patients and methods Thirty-two participants were recruited and IOP measured by rebound tonometer in pre, mid, and full pupillary dilation phases. Lens vault (LV at horizontal and vertical), angle opening distance (AOD at 500 and 750 μm) and trabecular iris space area (TISA at 500 and 750 μm) in temporal and nasal scans were quantified. Paired t test performed to establish a statistical significance P value less than or equal to 0.05. Statistical analysis used MS Excel. Results A total of 32 participants with mean age of 47.5±10.94 years consisting of 17 (53.13%) males and 15 (46.87%) females with 20 (62.5%) right and 12 (37.5%) left eyes were investigated. Mean IOP in pre, mid, and full-dilation phases were 14.86±2.87, 15.94±2.72, and 15.63±2.69 mmHg. Predilation IOP with IOP in mid and full dilation showed statistical significance (P=0.0001, 95% confidence interval 0.56–1.56) and 0.88 and 0.85 Pearson’s coefficients, respectively. IOP analysis with LV, AOD, and TISA in pre, mid, and full-dilation phases exhibited a significant difference (P<0.0001). Conclusion This research highlights an increase in IOP alongside a noteworthy decrease in the average LV by 30.94 μm during mid-dilation compared to the predilation phase. Likewise, the AOD at 750 μm demonstrated a significant reduction by 0.40 and 0.45 μm in temporal scans during mid and full dilation, respectively, while TISA remained unchanged.